This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
1.- 9 5 1 9 9 9 ≡ ( − 5 ) 1 9 9 9 ( m o d 1 0 0 ) Now, it can be proved by induction that ∀ n ≥ 2 , 5 n ends in 2 5 . So
9 5 1 9 9 9 ≡ ( − 5 ) 1 9 9 9 ≡ − 2 5 ≡ 7 5 ( m o d 1 0 0 )
2.- 9 6 ≡ 0 ( m o d 4 ) ⇒ 9 6 1 9 9 9 ≡ 0 ( m o d 4 ) . I'm going now to use Euler theorem . ( ϕ ( 2 5 ) = 2 0 ) and due to 2 1 and 2 5 are coprime 2 1 2 0 ≡ 1 ( m o d 2 5 ) ⇒ 9 6 1 9 9 9 ≡ 2 1 1 9 9 9 = ( 2 1 2 0 ) 9 9 ⋅ 2 1 1 9 ≡ 2 1 1 9 ≡ − 4 1 9 = − ( 4 5 ) 3 ⋅ 4 4 ≡ 6 ( m o d 2 5 ) ( 4 5 ≡ − 1 ( m o d 2 5 ) ). In this point, we can use Chinese Remainder theorem ⇒ 9 6 1 9 9 9 ≡ 4 ⋅ 1 9 ⋅ 6 + 0 ⋅ 2 5 ⋅ 1 = 4 5 6 ≡ 5 6 ( m o d 1 0 0 ) . Therefore, 9 5 1 9 9 9 + 9 6 1 9 9 9 ≡ 7 5 + 5 6 ≡ 3 1 ( m o d 1 0 0 )
Problem Loading...
Note Loading...
Set Loading...
Note that, 9 5 2 = 2 5 m o d ( 1 0 0 ) and 2 5 2 = 2 5 m o d ( 1 0 0 ) . Thus, 9 5 1 9 9 9 = 9 5 × ( 9 5 2 × 9 5 2 × … × 9 5 2 ) m o d ( 1 0 0 ) = 9 5 × 2 5 = 7 5 m o d ( 1 0 0 ) Again, 9 6 5 = 7 6 m o d ( 1 0 0 ) and 7 6 2 = 7 6 m o d ( 1 0 0 ) . Thus, 9 6 1 9 9 9 = 9 6 4 × ( 9 6 5 × 9 6 5 × … × 9 6 5 ) m o d ( 1 0 0 ) = 5 6 × 7 6 m o d ( 1 0 0 ) = 5 6 m o d ( 1 0 0 ) Thus the answer is 7 5 + 5 6 m o d ( 1 0 0 ) = 3 1 . ■